Factors of traffic congestion: A study of Penang Bridge in Malaysia - Lee, Wai Kit; Melan, Mustakim (2012)
The research aims to identify the factors of traffic congestion in Penang Bridge.The factors which will be discussed are bad driver behavior, poor bridge structure, and increasing number of vehicles.Bad driver behaviors such as distraction are contributed to road accidents which will lead to traffic congestions. Poor bridge structure discussed here is merges road, which is when the number of lanes narrowed from three lanes to two lanes when reaching the exit on each side of the bridge. Lastly, statistically shows that the increased of vehicles in Penang does directly caused traffic congestions in Penang Bridge.